Mechanistic view into the therapeutic effect, anticancer potential and the adverse effect of aspirin - Ouyang Juan (MATEC Web of Conferences)
In this research, the working mechanism behind the therapeutic effect of aspirin will be discussed in detail. Aspirin will also be assessed as a promising drug to treat cancerous cells in the future. Despite being demonstrated that aspirin has excellent efficacy in CVD treatment, the application of aspirin still faces numerous challenges, including aspirin resistance and the bleeding effect induced by the administration of aspirin. The chemistry behind the resistance against aspirin will be discussed and analysed. To cope with aspirin resistance, some diagnosing methods for aspirin resistance are introduced and some other alternative treatment schemes will also be discussed and compared with the traditional aspirin treatment. Bleeding risk is another severe adverse effect that might occur when long-term low-dose aspirin is applied. Through a large number of current studies, the bleeding risks that the administration of aspirin imposing on the upper gastrointestinal tract and the lower gastrointestinal tract are analysed. The relevance among the dose of aspirin, the frequency of the aspirin dose, the duration of the dosing period of aspirin administration and the bleeding risk induced by aspirin is deduced by analysing the experimental observations extracted from several clinical trials focusing on these factors.